Imatinib for bleomycin induced pulmonary toxicity: a case report and evidence‐base review. Issue 5 (1st April 2016) - Banakh, Iouri; Lam, Alice; Tiruvoipati, Ravindranath; Carney, Ian; Botha, John
Key Clinical Message: The evidence supporting therapy with imatinib for bleomycin‐induced pneumonitis (BIP) is equivocal. Further experience is needed to establish its role in BIP management. While it may be considered in the management of BIP, it is important to be mindful of the adverse effects including thrombocytopenia and gastrointestinal bleeding. Abstract : The evidence supporting therapy with imatinib for bleomycin‐induced pneumonitis (BIP) is equivocal. Further experience is needed to establish its role in BIP management. While it may be considered in the management of BIP, it is important to be mindful of the adverse effects including thrombocytopenia and gastrointestinal bleeding.